Papain-Catalyzed Synthesis of Polyglutamate Containing a Nylon Monomer Unit - Kenjiro Yazawa; Keiji Numata (Polymers, 2016)
Peptides have the potential to serve as an alternative for petroleum-based polymers to support a sustainable society. However, they lack thermoplasticity, owing to their strong intermolecular interactions. In contrast, nylon is famous for its thermoplasticity and chemical resistance. Here, we synthesized peptides containing a nylon unit to modify their thermal properties by using papain-catalyzed chemoenzymatic polymerization. We used l-glutamic acid alkyl ester as the amino acid monomer and nylon 1, 3, 4, and 6 alkyl esters as the nylon unit. Papain catalyzed the copolymerization of glutamic acid with nylon 3, 4, and 6 alkyl esters, whereas the nylon 1 unit could not be copolymerized. Other proteases used in this study, namely, bromelain, proteinase K, and Candida antarctica lipase (CALB), were not able to copolymerize with any nylon units. The broad substrate specificity of papain enabled the copolymerization of l-glutamic acid with a nylon unit. The peptides with nylon units demonstrated different thermal profiles from that of oligo(l-glutamic acid). Therefore, the resultant peptides with various nylon units are expected to form fewer intermolecular hydrogen bonds, thus altering their thermal properties. This finding is expected to broaden the applications of peptide materials and chemoenzymatic polymerization.